Challenges and Solutions to Instilling Islamic Moral Values among Learners in Institutions of Higher Learning in Uganda: A Case Study of Islamic University in Uganda - Hassan, Dr. Amina; Rehema, Kaggwa (International Journal of Scientific Research and Management (IJSRM), 2022)
This study investigated the challenges and solutions to instilling Islamic moral values among learners in institutions of higher learning: A case study of Islamic University in Uganda. The study was qualitative and used a case study design. The population of the study consisted of 25 da'wah (call to good) committee members. A sample consisted of 13 respondents, obtained through Simple random sampling. The 13 respondents sampled were arrived at after data saturation. The methods of Data collection were interviews and documentary review. The method of data analysis is the content method. Findings revealed that the institution faced the following challenges when instilling Islamic moral values; inadequate manpower, different background, militaristic approach, administrators' value dilemma, cultural diversity, the influence of Western culture, and Technology. The suggested solutions include; dialogue, teamwork, the use of hikmah (wisdom), respect for all, and disciplinary action. The study recommended implementing the suggested solutions to improve the challenges in instilling moral values among.